Correlation Between The Level Of Knowledge Of The Family Heads Regarding Dengue Hemorrhagic Fever Risks With 3m Plus Prevention Efforts In The Working Area Of Oesapa Public Health Center - Hana Ivena Bulo; S. M. J. Koamesah; Maria Agnes Etty Dedy (Cendana Medical Journal, 2025)
Dengue Hemorrhagic Fever (DHF) is a tropical infectious disease caused by the dengue virus, which is transmitted by the Aedes aegypti mosquito and often leads to outbreaks. One of the key efforts to prevent DHF is through the implementation of the 3M Plus strategy. A critical factor influencing the effectiveness of 3M Plus prevention efforts is the level of public knowledge regarding the dangers of DHF. Knowledge serves as a foundation for community-based prevention, starting from the most basic social unit—the family. As the primary decision-maker, the head of the family is considered important in possessing adequate knowledge about DHF prevention to protect their family members from infection. This study aims to examine the relationship between the knowledge level of family heads regarding the dangers of DHF and the implementation of the 3M Plus prevention strategy in the working area of the Oesapa Community Health Center. This research used an analytical survey method with a cross-sectional design. The study population included all family heads in the Oesapa Health Center's working area. Samples were selected using systematic random sampling, resulting in a total of 100 respondents. Statistical analysis was conducted using the Chi-Square test via SPSS software. The results showed that most family heads had good knowledge about the dangers of DHF, and there was a significant relationship between their knowledge level and the implementation of the 3M Plus prevention strategy in the Oesapa Health Center working area (p ≤ 0.05).